THE INFLUENCE OF SCIENTIFIC APPROACH AND CONTEXTUAL APPROACH ON MATHEMATICS LEARNING OUTCOMES OF CLASS VII STUDENT SMP NEGERI 2 JERUKLEGI - Dessy Dwi Capriati; Abdul Taram (Universitas Ahmad Dahlan, 2017)
Learning activity in SMP Negeri 2 Jeruklegi, Cilacap Regency at mathematics still being dominated by teachers and make students passive in class. This condition has made students in trouble and influence the learning outcomes. The purpose of this study is to know differences in mathematics learning outcomes using scientific, contextual and conventional approaches, and compare what is better to student grade VII mathematics learning outcomes in SMP Negeri 2 Jeruklegi in Cilacap Regency in 2015/2016 academic year. Â The population in this study is student grade VII at SMP Negeri 2 Jeruklegi, Cilacap Regency of even semester in the 2015/2016 academic year, which is split into seven classes and total students are 222. Sample is taken three classes using a random sampling technique, VII C as experiment class of scientific approach, VII E as experiment class of contextual approach, and VIII D as experiment class of conventional approach. Data collected by documentation and test. This study using experimental with perfect random design. The instrument test includes a validity test, reliability test, and the difference test. Data analysis to condition test include normality test with formula Chi-Quadrate, Homogeneity test with Bartlett Test, and hypothesis test using variance analysis and average test after anava. Based on variance analysis with significance level Î±= 5%, df numerator v1= 2 and df denominator v2= 92 show that: there is difference between mathematics learning outcomes of students using scientific approach, contextual and conventional approach those are showed by Fcount= 6,303458 > Ftable= 3,09543 and based on RNK test, obtained that contextual approach is better than mathematics learning using scientific and conventional approach to studentsâ€™ mathematics learning outcomes.